2016
DOI: 10.1515/med-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial amyloidosis mimicking bronchial asthma: a case report and review of the literature

Abstract: AbstractAmong two tracheobronchial forms (local and diffuse) and two parenchymal forms (nodular and alveolar septal) that were reported in previous literature, localized endobronchial amyloidosis is an uncommon disease of unknown cause. Bronchial amyloid deposits can occur as focal nodules or multifocal infiltration of the submucosa. We report the case of a 47-year-old man who had complained of dyspnea and wheezing for 1 month and who had been treated for severe asthma at anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It represents only 0.5 % of all symptomatic tracheobronchial lesions and is rarely associated with systemic amyloidosis. 2 , 3 , 4 …”
mentioning
confidence: 99%
“…It represents only 0.5 % of all symptomatic tracheobronchial lesions and is rarely associated with systemic amyloidosis. 2 , 3 , 4 …”
mentioning
confidence: 99%
“…Recurrent haemoptysis warranted further investigation with imaging, bronchoscopy, and biopsy which confirmed TBA (as seen in the first and third cases). There have been few case reports where patients have been initially misdiagnosed as asthma and later found to have multiple endobronchial nodules diagnosed as amyloid [6]. Solitary endobronchial amyloidosis having a nodular appearance is present in 14% of patients and can mimic endobronchial tumour [7].…”
Section: Discussionmentioning
confidence: 99%
“…AL is associated with primary systemic amyloidosis, myeloma-associated amyloid, and most localized forms of amyloid. AA is associated with secondary amyloidosis [ 2 ]. Amyloid deposits commonly affects males (2:1) of middle age group (50–60 years) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serraj et al reported a case of TBA involving trachea that was misdiagnosed as asthma [ 6 ]. In a case reported by Kang et al initially misdiagnosed as asthma, it was found to have multiple endobronchial nodules involving right upper, left upper and left lower lobe [ 2 ]. In our case also, there was a delay in diagnosis due the masquerading symptoms of poorly controlled asthma exacerbations for two years, after which he which found to have solitary endobronchial amyloid nodule in left upper lobe as a result of workup for persistent dyspnea and wheezing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation